Experiences of nurses and other health workers participating in a reflective course on compassion-based care. (8th August 2019) - Donald, Graeme; Wilson, Ian; McCarthy, Jodie; Hall, Ian; Crossley, Brenda; Adshead, Paula; Shaw, Vanessa; Dunne, Ross; Dwyer, Trish
Abstract : Background: the risk of compassion fatigue in healthcare staff is real, especially when considering the current financial pressures. A course in compassion-based care (CBC) was delivered to mental health staff at a hospital in north-west England, with the intention of rehabilitating ward culture and, subsequently, improving patient experience. Aims: to explore staff experiences of participating in the CBC course. Methods: a qualitative study using semi-structured interviews with participants ( n =12) was conducted. All staff attending the course were eligible and were invited to participate. Interview transcripts were thematically analysed. Findings: five themes characterising participant experience emerged from the data: meeting a need; creating the space; reorientation; prioritising self-care; and influencing team dynamics. Data overwhelmingly indicated the success of the CBC course. Conclusion: the CBC course appeared to have a profound effect on participants; it should be considered for further rollout and evaluation.